Coupled dissolution-precipitation reactions as a potential method for mitigating contaminant transport in carbonate aquifers. (November 2021) - Cohen, Anat; Grayevsky, Roni; Israeli, Yoni; Emmanuel, Simon
HIGHLIGHTS: Coupled dissolution-precipitation reactions can reduce porosity and permeability in porous media. Injection of oxalic acid into a calcitic 2D flow-through cell caused the formation of a barrier that limited solute transport and fluid flow. Such a method could be used to contain contaminant transport in calcareous aquifers. ABSTRACT: Subsurface barriers are often used to mitigate the spread of contaminants in groundwater. Current methods typically involve the injection of slurries into aquifers, a process that clogs porosity and reduces hydraulic conductivity. An alternative way to achieve this effect in calcareous aquifers could be to inject a fluid that dissolves the existing carbonate minerals and induces the formation of phases that have higher molar volumes. While such mineral replacement reactions are known to affect hydraulic conductivity, their ability to impede contaminant transport has not been tested. In this study, we injected oxalic acid into a pseudo-2D flow through cell containing calcitic sand, which simulated a calcareous aquifer. The oxalic acid causes the dissolution of calcite, as well as the precipitation of calcium oxalate minerals, in a reaction zone that spreads out from the point of injection. We found that this process reduces the water discharge in the cell by up to 80%, and caused the flow velocity around the reaction zone to drop from 20 cm h −1 to <0.1 cm h −1 . Mineralogical analyses and electron microscopy indicate that permeability is reduced primarily by partitioning of the intergranular voids by micrometer sized calcium oxalate crystals. Our results suggest that coupled dissolution-precipitation reactions could be a feasible method for deploying subsurface barriers in aquifers. Graphical Abstract: Image, graphical abstract